Preparation, Characterization And Performance Of La Doped Sno2 Catalytic Pellet For Detection Of Volatile Organic Compounds - Ang, Gaik Tin (2010)
SnO2 catalytic pellets doped with 0-10 atomic % lanthanum were developed by sol gel method and characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), surface analysis (Nitrogen adsorption-desorption) and scanning electron microscope (SEM). Prior the gas sensor measurement, LabVIEW software was programmed to interface with the electrometer to get all measured electrical resistance values. The electrical resistance change of the catalytic pellets was investigated using volatile organic compound (VOC) vapours i.e. ethanol, acetone and methanol in the air at the temperatures between 150-350oC.